Given that a, b, and c form an arithmetic progression and x, y, and z form a geometric progression, what is the sum of (b-c) log x + (c-a) log y + (a-b) log z ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let a = b+d = c+2d
Let x = u Therefore.. y=ur , x = u r 2
Sub these into the equation:
= -(d)log(x) + (2d)log(y) - (d)log(z) = d(2log(y) - log(x) - log(y)
= d(2log(ur) - log(u) - log( u r 2 )
= d l o g ( u ∗ u r 2 ( u r ) 2 )
= d(0) = 0